Protein kinase C epsilon is a key regulator of mitochondrial redox homeostasis in acute myeloid leukemia - Di Marcantonio, Daniela; Martinez, Esteban; Sidoli, Simone; Vadaketh, Jessica; Nieborowska-Skorska, Margaret; Gupta, Anushk; Meadows, Jake M.; Ferraro, Francesca; Masselli, Elena; Challen, Grant A.; Milsom, Michael; Scholl, Claudia; et al. (Clinical cancer research, 2018)
Purpose: The intracellular redox environment of acute myeloid leukemia (AML) cells is often highly oxidized compared to healthy hematopoietic progenitors and this is purported to contribute to disease pathogenesis. However, the redox regulators that allow AML cell survival in this oxidized environment remain largely unknown. - Experimental Design: Utilizing several chemical and genetically-encoded redox sensing probes across multiple human and mouse models of AML, we evaluated the role of the serine/threonine kinase PKC-epsilon (PKCε) in intracellular redox biology, cell survival and disease progression. - Results: We show that RNA interference-mediated inhibition of PKCε significantly reduces patient-derived AML cell survival as well as disease onset in a genetically engineered mouse model (GEMM) of AML driven by MLL-AF9. We also show that PKCε inhibition induces multiple reactive oxygen species (ROS) and that neutralization of mitochondrial ROS with chemical antioxidants or co-expression of the mitochondrial ROS-buffering enzymes SOD2 and CAT, mitigates the anti-leukemia effects of PKCε inhibition. Moreover, direct inhibition of SOD2 increases mitochondrial ROS and significantly impedes AML progression in vivo. Furthermore, we report that PKCε over-expression protects AML cells from otherwise-lethal doses of mitochondrial ROS-inducing agents. Proteomic analysis reveals that PKCε may control mitochondrial ROS by controlling the expression of regulatory proteins of redox homeostasis, electron transport chain flux, as well as outer mitochondrial membrane potential and transport. - Conclusions: This study uncovers a previously unrecognized role for PKCε in supporting AML cell survival and disease progression by regulating mitochondrial ROS biology and positions mitochondrial redox regulators as potential therapeutic targets in AML. Clin Cancer Res; 1-11. ©2017 AACR.
Gesehen am 28.02.2020